Financing decisions and the "crowding out" effect the case of the Philippines - Gochoco, Maria S.
This study empirically assesses the relevance of the ?crowding out? effect in the case of a developing country, the Philippines. The finding of a ?crowding out? effect from the issue of government debt is not due to a lack of rationality.
Keywords: Budget deficits; Deficit financing; Finance, Public